2020
DOI: 10.1126/sciadv.aaz0359
|View full text |Cite
|
Sign up to set email alerts
|

Maternal exercise via exerkine apelin enhances brown adipogenesis and prevents metabolic dysfunction in offspring mice

Abstract: The obesity rate is rapidly increasing, which has been attributed to lack of exercise and excessive energy intake. Here, we found a previously unidentified explanation, due to lack of maternal exercise. In this study, healthy maternal mice were assigned either to a sedentary lifestyle or to exercise daily, and fetal brown adipose tissue (BAT) development and offspring metabolic health were analyzed. Compared to the sedentary group, maternal exercise enhanced DNA demethylation of Prdm16 promoter and BAT develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
114
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(120 citation statements)
references
References 43 publications
6
114
0
Order By: Relevance
“…Consistently, chronic Pyrapelin 13 treatment of obese and insulin-resistant mice enhances glucose uptake and mitochondrial biogenesis in skeletal muscle ( Dray et al, 2008 ). In our previous study, we found that ME enhanced apelin levels in fetal circulation and adipose tissues of both mothers and offspring ( Son et al, 2020 ). Consistently, we observed the elevation of apelin in fetal and offspring muscle in this study, which correlated with AMPK activation and enhanced DNA demethylation in the Ppargc1a promotor.…”
Section: Discussionmentioning
confidence: 93%
“…Consistently, chronic Pyrapelin 13 treatment of obese and insulin-resistant mice enhances glucose uptake and mitochondrial biogenesis in skeletal muscle ( Dray et al, 2008 ). In our previous study, we found that ME enhanced apelin levels in fetal circulation and adipose tissues of both mothers and offspring ( Son et al, 2020 ). Consistently, we observed the elevation of apelin in fetal and offspring muscle in this study, which correlated with AMPK activation and enhanced DNA demethylation in the Ppargc1a promotor.…”
Section: Discussionmentioning
confidence: 93%
“…In fact, mainly from animal models studies (as summarized in Figure 4 ), it is clear that an excessive pre-pregnancy and during pregnancy BMI, a maternal diet rich in fat and calories, together with high levels of circulating glucose and free fatty acids can promote adipogenesis in the fetus [ 26 , 27 , 28 , 29 , 30 ]. The maternal diet has an important role also during breastfeeding as if it is rich in fat it seems to reduce the thermogenic activity of BAT and the expression of UCP1 in newborn mice [ 50 ]. Instead, breastfeeding mice showed a better expression of UCP1 and may benefit from both AKGs and MFGM-PL promoting BeAT activation in iAT [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although not confirmed in humans yet, this study is very interesting both because the high-fat-diet given to mice is extremely common in Western society and because it suggests that the apelin system could be a potential therapeutic target [ 50 ]. In mice, exercise during pregnancy has also been shown to act on the offspring hypothalamus and WAT inflammatory pathways, reducing the pro-inflammatory IL-6 and ameliorating glucose metabolism [ 51 ].…”
Section: Pregnancy and Bat In Newborns: The Role Of Fetal Programmingmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that human BAT corresponds more closely to beige rather than brown fat in the mouse, but this is still a matter of some debate [ 57 ]. Interestingly, BAT development and metabolic health can be shaped during fetal development by maternal exercise [ 62 ].…”
Section: Brown White and Beige Adipose Tissuementioning
confidence: 99%